Sintered R-Fe-B permanent magnet and preparation method and application thereof

By optimizing the raw material composition and process flow of neodymium iron boron magnets, sintered R-Fe-B permanent magnets containing Ga-rich and Ga-leading phases were prepared, which solved the problem of degradation of existing magnets at high temperatures, and achieved high coercive force, excellent mechanical properties and simplified process effects.

CN119763964AActive Publication Date: 2025-04-04YANTAI ZHENGHAI MAGNETIC MATERIAL CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411972484.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing neodymium iron boron magnets are difficult to maintain high coercive force and excellent mechanical properties at high operating temperatures, and the process operation is complicated, making it difficult to effectively control the formation of Ga-rich phases.

Method used

By optimizing the composition and process flow of raw materials, sintered R-Fe-B permanent magnets containing Ga-rich and Ga-leading phases were prepared. Specific methods include controlling the oxygen content in the raw material, regulating the distribution of Ga elements through the airflow grinding process, and ensuring a reasonable proportion of Ga-rich and Ga-depleted phases in the grain boundary phase.

Benefits of technology

It significantly improves the coercive force and bending strength of the magnet, while also improving the resistivity, meeting the performance requirements at high operating temperatures, and simplifying process operations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119763964A_ABST
    Figure CN119763964A_ABST
Patent Text Reader

Abstract

The invention discloses a sintered R-Fe-B permanent magnet and a preparation method and application thereof.In the formula of the permanent magnet, the specific ratio of R to Cu to Ti to Zr to B is adopted, the oxygen content of a product in different stages is controlled, then optimized distribution of a face-centered cubic structure and a close-packed hexagonal structure is adjusted, then targeted intervention is conducted in the forming stages of a rich Ga phase and a poor Ga phase, and the sintering performance of the permanent magnet is improved. Reasonable distribution of a rich Ga phase and a poor Ga phase is guaranteed, and synchronous improvement of resistivity and magnetic performance is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rare earth permanent magnet materials and preparation thereof, and in particular relates to a sintered R-Fe-B permanent magnet and a preparation method and application thereof. Background Art

[0002] NdFeB is widely used in permanent magnet motors due to its high remanent magnetic density, high coercive force, and high magnetic energy product. In recent years, the rapid development of the high-end application market of rare earth permanent magnet materials has also promoted the innovation of NdFeB magnet preparation technology, especially the requirements for long-term service of magnets at high operating temperatures are getting higher and higher. Intrinsic coercive force (Hcj) is an important indicator of the ability of NdFeB magnets to resist thermal demagnetization. In theory, NdFeB magnets should have high coercive force to withstand the demagnetization field at high operating temperatures. At the same time, the requirements for mechanical properties such as bending strength and resistivity of magnets are also gradually increasing.

[0003] In recent years, optimizing the grain boundary phase structure is a research hotspot for improving the magnetic properties of NdFeB. By optimizing the grain boundary phase, non-ferromagnetic properties are formed at the grain boundary, thereby weakening the exchange coupling between hard magnetic grains and achieving the enhancement of the magnetic properties of NdFeB. Patent document CN114255951A uses the main-auxiliary dual alloy method to control the formation of Ga-rich and Cu-rich phases in the grain boundary phase to improve the coercive force of the magnet. However, this method requires controlling the formula ratio of the dual alloy, the process operation is relatively complicated, and there is no effective control of the Ga-rich phase, so it is not easy to obtain a high-performance product with a specific ratio characteristic. Summary of the invention

[0004] In order to improve the deficiencies of the prior art, the present invention provides a sintered R-Fe-B permanent magnet, the sintered R-Fe-B permanent magnet comprising a main phase grain and a grain boundary phase; the components of the main phase grain include R2T 14 B; the grain boundary phase is located between the main phase grains, and the grain boundary phase includes a Ga-rich phase and a Ga-poor phase; wherein,

[0005] The Ga-rich phase includes R, Fe, Ga and M elements, wherein, by mass ratio, R accounts for 50-75wt%, Fe accounts for 5-20wt%, Ga accounts for 5-25wt%, and M accounts for 1-6wt%;

[0006] The Ga-poor phase includes R, Fe, Ga and M elements, wherein: by mass ratio, R accounts for 30-60wt%, Fe accounts for 15-35wt%, Ga accounts for 0.01-1wt%, and M accounts for 15-35wt%;

[0007] R is a rare earth element; M is selected from one or more of Al, Zr, Ti, Cu, Co, Mn, and Nb.

[0008] According to an embodiment of the present invention, R is a rare earth element, which includes at least Nd. Further, R may also include at least one selected from the following rare earth elements: Y, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc.

[0009] According to an embodiment of the present invention, the Ga-rich phase is composed of R, Fe, Ga and M elements, wherein, by mass ratio, R accounts for 50-75wt%, Fe accounts for 5-20wt%, Ga accounts for 5-25wt%, and M accounts for 1-6wt%.

[0010] According to an embodiment of the present invention, the Ga-poor phase is composed of R, Fe, Ga and M, wherein, by mass ratio, R accounts for 30-60wt%, Fe accounts for 15-35wt%, Ga accounts for 0.01-1wt%, and M accounts for 15-35wt%.

[0011] According to an embodiment of the present invention, in the Ga-rich phase, R accounts for 60-72wt% by mass, for example, 60wt%, 62wt%, 64wt%, 66wt%, 68wt%, 70wt%, 71wt% or 72wt%.

[0012] According to an embodiment of the present invention, in the Ga-rich phase, Fe accounts for 10 to 18 wt% by mass, for example, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt% or 18 wt%.

[0013] According to an embodiment of the present invention, in the Ga-rich phase, Ga accounts for 8 to 20 wt% by mass, for example, 8 wt%, 10 wt%, 12 wt%, 14 wt%, 16 wt%, 17 wt%, 18 wt% or 20 wt%.

[0014] According to an embodiment of the present invention, in the Ga-rich phase, the proportion of M is 2-6 wt% by mass, for example, 2 wt%, 3 wt%, 4 wt%, 5 wt% or 6 wt%.

[0015] According to an embodiment of the present invention, in the Ga-poor phase, R accounts for 40-54wt% by mass, for example, 40wt%, 42wt%, 46wt%, 48wt%, 50wt%, 52wt%, 53wt% or 54wt%.

[0016] According to an embodiment of the present invention, in the Ga-poor phase, the proportion of Fe by mass ratio is 20-34wt%, for example, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 27wt%, 28wt%, 30wt%, 32wt% or 34wt%.

[0017] According to an embodiment of the present invention, in the Ga-poor phase, the proportion of Ga by mass ratio is 0.05-0.9wt%, for example, 0.05wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt% or 0.9wt%.

[0018] According to an embodiment of the present invention, in the Ga-poor phase, the proportion of M by mass ratio is 15 to 32 wt%, for example, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 20 wt%, 24 wt%, 26 wt%, 28 wt%, 30 wt%, 32 wt% or 34 wt%.

[0019] According to an embodiment of the present invention, the area ratio of the Ga-rich phase to all grain boundary phase regions is X1, and the area ratio of the Ga-poor phase to all grain boundary phases is X2, wherein,

[0020] 13%≤X1≤30%, preferably, 18%≤X1≤28%, for example, X1 is 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27% or 28%;

[0021] 60%≤X2≤80%, preferably, 64%≤X2≤79%, for example, X2 is 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78% or 79%;

[0022] And 0.20≤X1 / X2≤0.50, for example, X1 / X2 is 0.20, 0.25, 0.30, 0.35, 0.40, 0.45 or 0.50.

[0023] According to an embodiment of the present invention, the sintered R-Fe-B permanent magnet, calculated by mass ratio of 100%, includes the following components:

[0024] R: 27-33 wt%, R is a rare earth element, which includes at least Nd and at least one selected from the following rare earth elements: Y, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc;

[0025] B: 0.9-1.3wt%;

[0026] Ga: 0.2-0.5wt%;

[0027] M: 0.45-3wt%; selected from one or more of Al, Zr, Ti, Cu, Co, Mn, Nb,

[0028] The rest are Fe and impurities. Preferably, the impurities are unavoidable impurities.

[0029] According to an embodiment of the present invention, M includes at least Cu, and may also be selected from at least one of Al, Ga, Zr, Ti, Nb, and Mn;

[0030] In the permanent magnet, the Cu content is 0.35-1.1 wt%, preferably 0.35-1.0 wt%.

[0031] According to an embodiment of the present invention, M further includes at least one of Zr or Ti, and in the permanent magnet, the content of Zr or Ti is 0.08-0.15wt%, for example, 0.08wt%, 0.1wt%, 0.12wt%, 0.14wt% or 0.15wt%.

[0032] According to an embodiment of the present invention, in the permanent magnet, based on the mass of the permanent magnet, the mass percentage content of R is greater than 28.50wt% and less than 32.50wt%, for example, 29.0wt%, 29.5wt%, 30.0wt%, 30.5wt%, 31.0wt%, 31.5wt%, 32.0wt%, 32.5wt%.

[0033] According to an embodiment of the present invention, in the permanent magnet, based on the mass of the permanent magnet, the mass percentage content of B is greater than 0.90 wt % and less than 1 wt %, for example, 0.90 wt %, 0.95 wt %, or 1 wt %.

[0034] According to an embodiment of the present invention, in the permanent magnet, based on the mass of the permanent magnet, the mass percentage content of Ga is 0.25-0.35wt%, for example, 0.25wt%, 0.28wt%, 0.3wt%, 0.32wt%, 0.35wt%.

[0035] According to an embodiment of the present invention, in the permanent magnet, based on the mass of the permanent magnet, the content of M is, for example, 0.45wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 2.0wt%, 2.5wt% or 3.0wt%.

[0036] According to an embodiment of the present invention, the sintered R—Fe—B permanent magnet satisfies the following equations (1) and (2):

[0037] lg[R]+lg([Cu]+[Zr]+[Ti])-1.2*[B]≥0; (1)

[0038] 0.45≤[Cu]+[Zr]+[Ti]≤0.7; (2)

[0039] Wherein [R], [Cu], [Zr], [Ti] and [B] are the mass percentages of R, Cu, Zr, Ti and B respectively.

[0040] According to an embodiment of the present invention, [Cu]+[Zr]+[Ti] is 0.45, 0.5, 0.55, 0.6, 0.65 or 0.7.

[0041] The present invention also provides a method for preparing the sintered NdFeB permanent magnet, the method comprising:

[0042] The raw materials for preparing the sintered NdFeB permanent magnet are sequentially subjected to a smelting process, a powder making process, a pressing process and a heat treatment process to prepare the sintered NdFeB permanent magnet.

[0043] According to an embodiment of the present invention, in the smelting process, the oxygen content of the rare earth raw material R (for example, PrNd) used is a, the oxygen content of Fe is b, and the oxygen content of BFe is c;

[0044] a, b, c satisfy: a<200ppm, b<250ppm, c<450ppm.

[0045] Preferably, a is 40 to 180 ppm, and for example 50 to 150 ppm;

[0046] Preferably, b is 40 to 240 ppm, and for example, 70 to 220 ppm;

[0047] Preferably, c is 80 to 440 ppm, and for example, 120 to 300 ppm.

[0048] According to an embodiment of the present invention, the smelting process can be performed by a method known in the art, such as a method of rapidly solidifying and spinning a strip to produce alloy flakes. Exemplarily, the smelting process for preparing alloy flakes is as follows: each raw material is heated to 1300-1600° C. by electromagnetic induction to melt, and then the alloy melt is poured on a chill roll (preferably a polished chill roll), and the alloy flakes are obtained after cooling.

[0049] According to an embodiment of the present invention, the powder making process includes hydrogen embrittlement, intermediate grinding and / or air flow grinding, and air flow milling powder is obtained after the powder making process is completed. In the present invention, the hydrogen embrittlement, intermediate grinding and / or air flow grinding can be carried out by methods known in the art, as long as the air flow milling powder can be obtained.

[0050] According to an embodiment of the present invention, the oxygen content V in the airflow milling process is 25 to 150 ppm, preferably 40 to 140 ppm. Preferably, the airflow milling process can be introduced by introducing oxygen, and the oxygen-increasing method is not limited. An oxygen-containing gas can be introduced, for example, oxygen, air or compressed air can be introduced alone, a mixed gas of oxygen and argon can be introduced, a mixed gas of oxygen and nitrogen can be introduced, etc., as long as the oxygen content in the airflow mill grinding chamber is maintained within the range of 25 to 150 ppm.

[0051] According to an embodiment of the present invention, the temperature during the jet milling process is 30-40°C, for example, 30°C, 32°C, 34°C, 36°C, 38°C or 40°C.

[0052] Preferably, an antioxidant and / or lubricant may be added to the airflow milled powder obtained after the powder making process. The antioxidant and / or lubricant may be any antioxidant and / or lubricant known in the art, which is not specifically limited in the present invention. Alternatively, the antioxidant and / or lubricant may be selected from, for example, fatty acid esters. Further, the antioxidant and / or lubricant may be added in an amount of 0.1 to 1 wt % of the airflow milled powder, for example, 0.1 to 0.5 wt %.

[0053] According to an embodiment of the present invention, the oxygen content of the alloy flakes prepared in the smelting process is x (wt%), the oxygen content of the jet milled powder after the jet milling process is y (wt%), and the particle size D50 of the jet milled powder is z (μm), and the three should satisfy the following relations (3)-(6):

[0054] 0.12≥(y-2x)*z≥0.04; (3)

[0055] 0.025≥x≥0.003; (4)

[0056] 0.09≥y≥0.02; (5)

[0057] 4.5≥z≥2.3; (6).

[0058] If the present invention does not satisfy the range of the above relationship equations (3)-(6), the Ga-rich phase and the Ga-poor phase cannot be formed or the proportion of the formed Ga-rich phase and the Ga-poor phase is not within the specified range, which ultimately affects the magnetic properties and resistivity of the product.

[0059] According to an embodiment of the present invention, the pressing process can dry-form the mixture (or airflow milled powder): for example, the mixture is filled into a mold configured in a magnetic field and pressurized to form the mixture to obtain a molded body. At this time, by performing molding while applying a magnetic field, the mixture can be molded in a state where the crystal axis is oriented in a specific direction. In the pressing step, molding aids known in the art can be added as needed. Preferably, the pressure during pressurization can be greater than 8MPa and less than 300MPa; the applied magnetic field can be a static magnetic field and / or a pulsed magnetic field, and the magnetic field strength can be 2 to 5T. Alternatively, wet molding can also be used: for example, a slurry in which the mixture is dispersed in a solvent such as oil is molded to obtain a molded body.

[0060] Those skilled in the art will appreciate that there is no particular limitation on the specific shape of the molded body, which can be adjusted according to the application conditions of the permanent magnet. For example, the molded body can be a rectangular parallelepiped, a flat plate, a column, a ring, or a C-shaped shape.

[0061] According to an embodiment of the present invention, the conditions of the heat treatment process include: a sintering temperature of 900-1100° C. (for example, 1000° C.) and a sintering time of 2-8 h (for example, 3 h, 4 h, 5 h, 6 h, 7 h).

[0062] According to an embodiment of the present invention, after the heat treatment process, a diffusion process may be optionally performed.

[0063] According to an embodiment of the present invention, in the diffusion process, a diffusion source is used to diffuse the product after the heat treatment process. Preferably, the diffusion source includes a heavy rare earth element RH, and the heavy rare earth element is selected from at least one of gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium and yttrium, preferably terbium.

[0064] Preferably, in the diffusion source, the mass content of heavy rare earth elements is not less than 60%, preferably not less than 70%.

[0065] According to an embodiment of the present invention, in the diffusion process, a diffusion source is coated on the surface of the product of the heat treatment process to perform diffusion treatment.

[0066] Preferably, the diffusion process includes a first diffusion process and a second diffusion process;

[0067] The first diffusion treatment may be performed at a holding temperature of 800° C. to 1000° C. for 2 hours to 40 hours. The heating rate to the holding temperature may be 5° C. / min to 50° C. / min.

[0068] The second diffusion treatment may be performed at a holding temperature of 450° C. to 650° C. for 2 hours to 20 hours. The heating rate to the holding temperature may be 5° C. / min to 50° C. / min.

[0069] The present invention also provides the application of the above-mentioned permanent magnet in the fields of motors, speakers, magnetic separators, computer disk drives, magnetic resonance imaging equipment, etc., preferably in motors as motor rotor magnetic steel.

[0070] Beneficial Effects

[0071] The grain boundary phase of the present invention comprises a two-grain grain boundary and a triangular grain boundary; wherein the two-grain grain boundary is located between any two main phase grains, and the triangular grain boundary is located between any three or more main phase grains.

[0072] The present invention prepares alloy flakes with different oxygen contents by controlling the oxygen content in the raw materials. It is speculated that the alloy flakes with lower oxygen content can provide a low oxygen environment to promote the formation of the face-centered cubic structure in the grain boundary phase. Under conventional processes, a large proportion of the face-centered cubic structure in the grain boundary phase is located at the two-grain grain boundary, and only a small part exists at the triangular grain boundary; at the same time, due to the different lattice constants of the face-centered cubic structure and the close-packed hexagonal structure, the Ga element is concentrated in the face-centered cubic structure, and a high proportion of the Ga element can be obtained at the two-grain grain boundary. By introducing oxygen-containing gas into the air flow mill, the oxygen content in the air flow mill equipment is controlled within 25 to 150 ppm. Within the oxygen content range of the present invention, the proportion of the self-formed close-packed hexagonal structure in the triangular grain boundary or the proportion of the close-packed hexagonal structure transformed from the face-centered cubic structure increases, and the Ga element in the triangular grain boundary is transferred to the face-centered cubic structure at the two-grain grain boundary, which promotes the formation of a Ga-poor phase in the triangular grain boundary. The present invention combines the comprehensive regulation of particle size and formula, and finally realizes that the Ga content in the product has different proportions in different regions, forming different grain boundary phases with both Ga-rich phase regions and Ga-poor phase regions. It should be noted that although the addition of oxide powder can improve the distribution of Ga-rich phase, since oxide powder (such as metal oxide powder) cannot stably provide an oxygen-containing atmosphere, it cannot achieve the recombination of the close-packed hexagonal structure in the triangular grain boundary, which is not conducive to the regulation of the Ga-poor phase and cannot obtain better mechanical properties (bending strength, etc.), it is not recommended to add oxide powder as an oxygen enrichment process.

[0073] The R, Cu, Zr, Ti, and B in the raw materials satisfy the relationship lg[R]+lg([Cu]+[Zr]+[Ti])-1.2*[B]≥0, and the oxygen content of the raw materials is controlled in a coordinated manner, so that the area ratio of the Ga-rich phase to the grain boundary phase is 13%≤X1≤30%, which can significantly reduce the grain boundary energy with the main phase, thereby improving the magnetic properties of the product. When the Ga-rich phase area at the two-grain boundary is too large (such as greater than 30%), the excess Ga element will enter the main phase and form Nd2(Fe 1-x Ga x ) 14 B. The molecular magnetic moment decreases, the magnetic properties decline, and the lattice constant C increases, which in turn causes changes in the stress state inside the crystal. The macroscopic manifestation is that the bending strength of the product will deteriorate to a certain extent.

[0074] The present invention regulates the proportion of Ga-poor phase within the range of 60%-80%, and improves the resistivity of the product by affecting the interaction between atoms and the distribution of electronic states. In the airflow milling process stage, the oxygen content in the airflow milling equipment is controlled within 25-150ppm, which can regulate the Ga-poor phase formed by Ga elements in the grain boundaries while reducing the formation of oxides in the grain boundaries. When the oxygen content of the airflow milling powder is within the range of 0.02-0.09wt%, the permanent magnet has excellent mechanical properties (i.e., bending strength). If the oxygen atmosphere in the airflow milling stage is too large, a large amount of oxides will appear in the grain boundary phase, reducing the bonding force between the grain boundary phase and the main phase, causing the mechanical properties (bending strength) of the product to deteriorate. Through the airflow milling oxygen enrichment process, the area ratio of the Ga-poor phase region to the grain boundary phase is accurately controlled to be 60%≤X2≤80%, and the area ratio of the Ga-rich phase to the Ga-poor phase is controlled to be 0.20≤X1 / X2≤0.50, which can achieve a better resistivity while improving the magnet material.

[0075] The permanent magnet formula of the present invention adopts specific ratios of R, Cu, Ti, Zr and B to control the oxygen content of the product at different stages, thereby adjusting the optimal distribution of the face-centered cubic structure and the close-packed hexagonal structure, and then performing targeted intervention on the formation stages of the Ga-rich phase and the Ga-poor phase, thereby ensuring the reasonable distribution of the Ga-rich phase and the Ga-poor phase and achieving the simultaneous improvement of the resistivity and the magnetic properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] Figure 1 is a transmission electron microscope image of the Ga-rich phase of the permanent magnet of Example 1;

[0077] Figure 2 This is a transmission electron microscope image of the Ga-poor phase of the permanent magnet of Example 1. DETAILED DESCRIPTION

[0078] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0079] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0080] Test method:

[0081] The sintered NdFeB permanent magnets prepared in the following Examples 1-4 and Comparative Examples 1-6 of the present invention were tested for magnetic properties, oxygen content, bending strength, and resistivity. The testing equipment and method used are as follows:

[0082] Magnetic property test: NIM-62000 magnetic tester from China Institute of Metrology, 7-5-5mm standard test;

[0083] Oxygen content: analyzed by Gangyan Nano-Tech's oxygen, nitrogen and hydrogen analyzer.

[0084] Bending strength: universal mechanical testing machine, 35-5-5mm standard test;

[0085] Resistivity: Resistivity meter;

[0086] Area ratio calculation: Using a scanning transmission microscope JEOL-2010F, the grain boundary phase composition was analyzed at high magnification, and then in-situ observation was performed at low magnification. The ratio analysis of grain boundary phases with different contrasts was performed using Image-Pro Plus software.

[0087] Example 1

[0088] The sintered NdFeB magnet is prepared by the following preparation method:

[0089] (1) The preparation method of alloy flakes is as follows: the raw materials are configured according to the composition table of NdFeB materials in Table 1 (the unit is wt%), and the oxygen content in the selected PrNd, Fe, and BFe raw materials is shown in Table 2. The prepared raw materials are heated to 1400°C by electromagnetic induction until they are melted and then kept warm for 10 minutes, and then poured onto the surface of a quenching roller. After cooling, Re-Fe-B alloy flakes are obtained, and a small amount of alloy flakes are taken to test the oxygen content x.

[0090] (2) The alloy flakes obtained above are subjected to hydrogen absorption treatment, and then ground in a jet mill grinding chamber (the temperature of the jet mill grinding chamber is 31°C) with an oxygen content of 44 ppm (by introducing oxygen) to obtain jet mill powder with D50 = 3.2 μm. The jet mill powder and antioxidant fatty acid ester are mixed evenly in a mass ratio of 99.95:0.05 to obtain a uniformly mixed alloy powder.

[0091] (3) Filling the alloy powder into a pressing mold. The magnetic field orientation molding specifically includes: performing orientation pressing in a magnetic field with a field strength of 2T, and then performing cold isostatic pressing at 170MPa*10s to obtain the green body.

[0092] (4) The green compact is placed in a vacuum sintering furnace for sintering at a temperature of 1070°C and a sintering time of 4 h.

[0093] (5) The sintered compact is subjected to magnetron sputtering to arrange Tb on the surface of the substrate, and a diffusion heat treatment is performed. The diffusion heat treatment process includes: a primary heat treatment at a diffusion temperature of 920°C and a heat treatment time of 30 hours; followed by a secondary heat treatment at 510°C and a heat treatment time of 10 hours to obtain the rare earth permanent magnet of this embodiment.

[0094] Figure 1 This is a picture of the grain boundary phase taken under a high-magnification transmission electron microscope. The composition of the Ga-rich phase is R 65.9 Fe 15.2 Co 2.8 Cu 1.5 Ga 13.1 Zr 1.5 .

[0095] Figure 2 This is a picture of the grain boundary phase taken under a high-magnification transmission electron microscope. The composition of the Ga-poor phase is R 51.5 Fe 32.1 Co 8.6 Cu 5.2 Ga 0.9 Zr 1.7 .

[0096] Example 2

[0097] The preparation process of Example 2 is the same as that of Example 1, except that:

[0098] In step (1), the composition table of the NdFeB material of Example 2 is shown in Table 1 for the raw materials (all in wt%), and the oxygen content in the selected PrNd, Fe, and BFe raw materials is shown in Table 2 for details.

[0099] In step (2), the temperature of the jet mill grinding chamber is 31° C., and air is introduced so that the oxygen content in the jet mill grinding chamber is 65 ppm.

[0100] Example 3

[0101] The preparation process of Example 3 is the same as that of Example 1, except that:

[0102] In step (1), the composition table of the NdFeB material of Example 3 is shown in Table 1 for the raw materials (all in wt%), and the oxygen content in the selected PrNd, Fe, and BFe raw materials is shown in Table 2 for details.

[0103] In step (2), the temperature of the jet mill grinding chamber is 33° C., and compressed air is introduced to make the oxygen content in the jet mill grinding chamber 117 ppm, thereby obtaining jet mill powder with D50=3.6 μm.

[0104] Example 4

[0105] The preparation process of Example 4 is the same as that of Example 1, except that:

[0106] In step (1), the composition table of the NdFeB material of Example 4 is shown in Table 1 for the raw materials (all in wt%), and the oxygen content in the selected PrNd, Fe, and BFe raw materials is shown in Table 2 for details.

[0107] In step (2), the temperature of the jet mill grinding chamber is 36°C, and a mixed gas with a volume ratio of air to nitrogen of 1:1 is introduced so that the oxygen content in the jet mill grinding chamber is 133 ppm, and jet mill powder with D50 = 3.6 μm is obtained.

[0108] Comparative Example 1

[0109] The preparation process of Comparative Example 1 is the same as that of Example 1, except that:

[0110] In step (1), the composition table of the NdFeB material of Comparative Example 1 is shown in Table 1 for the raw materials (all in wt%), and the oxygen content in the selected PrNd, Fe, and BFe raw materials is shown in Table 2 for details.

[0111] In step (2), the temperature of the jet mill grinding chamber is 34° C., and oxygen is introduced so that the oxygen content in the jet mill grinding chamber is 38 ppm.

[0112] Comparative Example 2

[0113] The preparation process of Comparative Example 2 is the same as that of Example 1, except that:

[0114] In step (1), the composition table of the NdFeB material of Comparative Example 2 is shown in Table 1 for the raw materials (all in wt%), and the oxygen content in the selected PrNd, Fe, and BFe raw materials is shown in Table 2 for details.

[0115] In step (2), the temperature of the airflow mill grinding chamber is 36° C., no oxygen-containing gas is introduced into the airflow mill grinding chamber, and the oxygen content in the airflow mill chamber is 15 ppm.

[0116] Comparative Example 3

[0117] The preparation process of Comparative Example 3 is the same as that of Example 1, except that:

[0118] In step (1), the composition table of the NdFeB material of Comparative Example 3 is shown in Table 1 for the raw materials (all in wt%), and the oxygen content in the selected PrNd, Fe, and BFe raw materials is shown in Table 2 for details.

[0119] In step (2), the temperature of the jet mill grinding chamber is 33° C., and oxygen is introduced so that the oxygen content in the jet mill grinding chamber is 176 ppm, thereby obtaining jet mill powder with D50=4.2 μm.

[0120] Comparative Example 4

[0121] The preparation process of Comparative Example 4 is the same as that of Example 1, except that:

[0122] In step (1), the composition table of the NdFeB material of Comparative Example 4 is shown in Table 1 for the raw materials (all in wt%), and the oxygen content in the selected PrNd, Fe, and BFe raw materials is shown in Table 2 for details.

[0123] In step (2), the temperature of the jet mill grinding chamber is 36° C., and oxygen is introduced so that the oxygen content in the jet mill grinding chamber is 107 ppm.

[0124] Comparative Example 5

[0125] The preparation process of Comparative Example 4 is the same as that of Example 1, except that:

[0126] In step (1), the composition table of the NdFeB material of Comparative Example 4 is shown in Table 1 for the raw materials (all in wt%), and the oxygen content in the selected PrNd, Fe, and BFe raw materials is shown in Table 2 for details.

[0127] In step (2), the temperature of the jet mill grinding chamber is 31° C., and oxygen is introduced into the grinding chamber to make the oxygen content of the jet mill grinding chamber 121 ppm, thereby obtaining jet mill powder with D50=5.0 μm.

[0128] Comparative Example 6

[0129] The preparation process of Comparative Example 4 is the same as that of Example 1, except that:

[0130] In step (1), the composition table of the NdFeB material of Comparative Example 4 is shown in Table 1 for the raw materials (all in wt%), and the oxygen content in the selected PrNd, Fe, and BFe raw materials is shown in Table 2 for details.

[0131] In step (2), the temperature of the jet mill grinding chamber is 32° C., and oxygen is introduced so that the oxygen content in the jet mill grinding chamber is 100 ppm, thereby obtaining jet mill powder with D50=3.5 μm.

[0132] Table 1 Permanent magnet raw materials and proportions (wt%) of Examples 1-4 and Comparative Examples 1-6

[0133]

[0134]

[0135] Table 2 Oxygen content a in the permanent magnet raw materials PrNd, oxygen content b in Fe, oxygen content c in BFe, oxygen content V in the jet mill grinding chamber, oxygen content x in the alloy flakes, oxygen content y in the jet mill powder, and particle size D50z in the jet mill powder of Examples 1-4 and Comparative Examples 1-6

[0136] a(ppm) b(ppm) c(ppm) V(ppm) x(wt%) y(wt%) z(μm) (y-2x)*z Example 1 58 125 213 44 0.0047 0.0250 3.2 0.0498 Example 2 98 81 147 65 0.0035 0.0340 3.2 0.0864 Example 3 77 170 285 117 0.0103 0.0455 3.6 0.0898 Example 4 133 215 269 133 0.0168 0.0615 3.6 0.1004 Comparative Example 1 265 317 350 38 0.0287 0.0375 3.2 -0.0637 Comparative Example 2 122 118 150 15 0.0091 0.0160 3.2 -0.0070 Comparative Example 3 100 165 194 176 0.0113 0.1260 4.2 0.4345 Comparative Example 4 91 177 209 107 0.0109 0.0325 3.2 0.0342 Comparative Example 5 99 103 187 121 0.0098 0.0464 5.0 0.1340 Comparative Example 6 124 178 325 100 0.0186 0.048 3.5 0.0378

[0137] Table 3 Permanent magnet properties, resistivity, and flexural strength of Examples 1-4 and Comparative Examples 1-6

[0138]

[0139]

[0140] By comparing Comparative Example 1 with Example 1, due to the selection of oxygen content in raw material control, the oxygen content of the alloy flakes in Comparative Example 1 is relatively high, and does not satisfy the relationship (3) of 0.12≥(y-2x)*z≥0.04, resulting in the proportion of Ga-rich phase in the product of Comparative Example 1 being too low. Furthermore, the coercive force of Comparative Example 1 is significantly lower than that of Example 1.

[0141] In Comparative Example 2, oxygen-containing gas was not introduced during the air flow milling process, and the oxygen content in the air flow mill grinding chamber was 15 ppm. At this time, the Ga element was still overly concentrated in the two-grain grain boundary phase, and sufficient Ga-poor phase could not be produced in the triangular grain boundary, so that the area ratio of the Ga-poor phase region in the product of Comparative Example 2 to the grain boundary phase was 58%, and the resistivity of the product of Comparative Example 2 was significantly reduced.

[0142] In Comparative Example 3, an excessive amount of oxygen-containing gas was introduced during the jet milling process, the oxygen content in the jet milling chamber was 176 ppm, and the oxygen content of the jet milled powder obtained was 0.1260 wt %. The excessive oxygen content in the jet milling chamber not only generated a high proportion of Ga-poor phase, but also caused the magnet to generate more oxides, resulting in a significant deterioration of the flexural strength.

[0143] In comparative example 4, in the composition table configuration of NdFeB material, the content of Cu element in the raw material is 0.3wt%, and the ratio of the raw materials does not satisfy the relationship lg[R]+lg([Cu]+[Zr]+[Ti])-1.2*[B]≥0. The reduction of Cu element reduces the distribution competition between Cu and Ga in the grain boundary, and excessive Ga enters the main phase. The area ratio of Ga-rich phase region to grain boundary phase is too high, and Nd2(Fe2O3) appears in the main phase of NdFeB. 1-x Ga x ) 14 In phase B, the magnetic properties decrease and the bending strength of the magnet is significantly deteriorated.

[0144] In Comparative Example 5, as the particle size of the air flow mill increases, the surface energy of the magnetic powder decreases. Even if the oxygen enrichment process is adopted, under the oxygen content atmosphere of 121ppm in the air flow mill grinding chamber, the product of Comparative Example 5 is still not enough to make the Ga element in the triangular grain boundary tend to move to the two grain boundaries, and the diluted Ga-poor phase of the triangular grain boundary cannot be obtained, so that the area ratio of the Ga-poor phase region in the product of Comparative Example 5 to the grain boundary phase is 58%, and the resistivity of the product of Comparative Example 5 is significantly reduced.

[0145] In Comparative Example 6, in the composition table configuration of the NdFeB material, the content of the Zr element in the raw material is 0.3wt%, which leads to an increase in the proportion of ZrB2 in the grain boundary phase, so that the ratio of the Ga-rich phase area to the Ga-poor phase area in the grain boundary phase is 0.19, which does not meet the area ratio of the Ga-rich phase to the Ga-poor phase (0.20≤X1 / X2≤0.50) of the present application, resulting in the coercive force Hcj of Comparative Example 6 being significantly lower than that of Example 1.

[0146] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A sintered R-Fe-B permanent magnet, characterized in that: The sintered R-Fe-B permanent magnet comprises main phase grains and grain boundary phase; the components of the main phase grains include R2T 14 B; the grain boundary phase is located between the main phase grains, and the grain boundary phase includes a Ga-rich phase and a Ga-poor phase; wherein, The Ga-rich phase includes R, Fe, Ga and M elements, wherein, by mass ratio, R accounts for 50-75wt%, Fe accounts for 5-20wt%, Ga accounts for 5-25wt%, and M accounts for 1-6wt%; The Ga-poor phase includes R, Fe, Ga and M elements, wherein: by mass ratio, R accounts for 30-60wt%, Fe accounts for 15-35wt%, Ga accounts for 0.01-1wt%, and M accounts for 15-35wt%; R is a rare earth element; M is selected from one or more of Al, Zr, Ti, Cu, Co, Mn and Nb.

2. The permanent magnet according to claim 1, characterized in that The area ratio of Ga-rich phase to grain boundary phase is X1, and the area ratio of Ga-poor phase to grain boundary phase is X2, where: 13%≤X1≤30%; 60%≤X2≤80%; And 0.20≤X1 / X2≤0.

50.

3. The permanent magnet according to claim 1, characterized in that The sintered R-Fe-B permanent magnet, calculated by mass ratio as 100%, comprises the following components: R: 27-33 wt%, R is a rare earth element, which includes at least Nd and at least one selected from the following rare earth elements: Y, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc; B: 0.9-1.3wt%; Ga: 0.2-0.5wt%; M: 0.45-3wt%; selected from one or more of Al, Zr, Ti, Cu, Co, Mn, Nb, The rest is Fe and impurities.

4. The permanent magnet according to claim 3, characterized in that M includes at least Cu, and may also be selected from at least one of Al, Ga, Zr, Ti, Nb, and Mn; In addition, the content of Cu in the permanent magnet is 0.35-1.1 wt%. Preferably, M further includes at least one of Zr and Ti, and the content of Zr or Ti in the permanent magnet is 0.08-0.15 wt%.

5. The permanent magnet according to claim 1, characterized in that The sintered R-Fe-B permanent magnet satisfies the following equations (1) and (2): lg[R]+lg([Cu]+[Zr]+[Ti])-1.2*[B]≥0; (1) 0.45≤[Cu]+[Zr]+[Ti]≤0.7; (2) Wherein [R], [Cu], [Zr], [Ti] and [B] are the mass percentages of R, Cu, Zr, Ti and B respectively.

6. The method for preparing a permanent magnet according to any one of claims 1 to 5, characterized in that: The method comprises: The raw materials for preparing the sintered NdFeB permanent magnet are sequentially subjected to a smelting process, a powder making process, a pressing process and a heat treatment process to prepare the sintered NdFeB permanent magnet.

7. The method according to claim 6, characterized in that In the smelting process, the oxygen content of the rare earth raw material R used is a, the oxygen content of Fe is b, and the oxygen content of BFe is c; a, b, c satisfy: a<200ppm, b<250ppm, c<450ppm.

8. The method according to claim 6, characterized in that The powder making process includes hydrogen embrittlement, intermediate grinding and / or air flow grinding, and air flow grinding powder is obtained after the powder making process is completed. Preferably, the oxygen content V during the jet milling process is 25 to 150 ppm. Preferably, the temperature during jet milling is 30-40°C.

9. The method according to claim 6, characterized in that The oxygen content of the alloy flakes prepared in the smelting process is x (wt%), the oxygen content of the jet milled powder after the jet milling process is y (wt%), and the particle size D50 of the jet milled powder is z (μm), and the three should satisfy the following relationship (3)-(6): 0.12≥(y-2x)*z≥0.04; (3) 0.025≥x≥0.003; (4) 0.09≥y≥0.02; (5) 4.5≥z≥2.3; (6)。 Preferably, the conditions of the heat treatment process include: a sintering temperature of 900 to 1100° C. and a sintering time of 2 to 8 hours. Preferably, after the heat treatment step, a diffusion step is optionally performed.

10. Application of the permanent magnet described in any one of claims 1 to 5 in the field of motors, loudspeakers, magnetic separators, computer disk drives or magnetic resonance imaging equipment, preferably in motors as motor rotor magnetic steel.

Citation Information

Patent Citations

  • R-Fe-B sintered magnet and making method

    CN107527699A

  • Sintered body, sintered permanent magnet and preparation method thereof

    CN110444386A

  • High-performance sintered neodymium-iron-boron magnet and preparation method thereof

    CN114255951A

  • Neodymium-iron-boron magnet and preparation method and application thereof

    CN114284018A

  • Sintered R-Fe-B permanent magnet and preparation method and application thereof

    CN115410786A